2015
DOI: 10.1039/c5ra08078a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of graphene oxide as dispersed phase in cement mortar matrix in defining the crystal patterns of cement hydrates and its effect on mechanical, microstructural and crystallization properties

Abstract: The influence of dispersed graphene oxide (GO) on the mechanical, microstructural and crystallization properties of GO–cement nanocomposites has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(75 citation statements)
references
References 40 publications
(36 reference statements)
1
70
0
4
Order By: Relevance
“…XRD is a technique used to determine the composition of crystalline phases in a material [30]. The presence of different phases present in samples was analysed using XRD (PANalytical XPERT-PRO Diffractometer) in 2h range between 10°and 70°.…”
Section: Xrd Analysis For Hydration Behaviourmentioning
confidence: 99%
“…XRD is a technique used to determine the composition of crystalline phases in a material [30]. The presence of different phases present in samples was analysed using XRD (PANalytical XPERT-PRO Diffractometer) in 2h range between 10°and 70°.…”
Section: Xrd Analysis For Hydration Behaviourmentioning
confidence: 99%
“…SiO 2 NPs with high specic surface area have been widely utilized to reinforce cement composites and have produced remarkable improvement in mechanical strength on account of nucleus effects and lling effects. 13 Moreover, SiO 2 NPs with pozzolanic activity can consume calcium hydroxide (CH) to form stable calcium silicate hydrate (C-S-H) gels.…”
Section: Introductionmentioning
confidence: 99%
“…However, the traditional reinforcements are either in the macro-scale or micro-scale; they can enhance the crackresistance in the macro/micro scale, but they fail to stop the initiation and propagation of nano-cracks. [1][2][3] Therefore, this creates a need to use a material with nano-size dimension as the reinforcing agent for cement-based materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But nanomaterial generally agglomerates due to the strong Van der Waal's forces at nano scale and reduced workability which may be due to adsorption of free water onto the surface of nanomaterial in concrete which may be overcome by a perfect combination of sonication for mechanical separation and compatible admixtures of the respective nanocomposites [1]. It has been observed that graphene oxide which is a monolayer of graphene with oxygen containing functional groups [5] has the ability to absorb water molecule producing a water reservoir and water transport channel for further hydration of cement, accelerates the hydration rate due to its catalytic behavior when added to cement as reinforcing material [2]. Effects of GO addition into cement matrix can effectively improve the transport properties in cement which eventually improve its durability (its transport properties reduce the movement of aggressive chemicals due to formation of strong barrier enhancing its resistance to aggressive elements).…”
mentioning
confidence: 99%